Occupational Hazards Exposure and Knowledge, Attitude and Practice towards Meat Safety amongst Abattoir Workers, Hawassa City, Southern Ethiopia - Tolera, Sina Temesgen; Mengistu, Dechassa Adere (International Journal of Occupational Safety and Health, 2021)
Introduction: Food-borne diseases and occupational problems due to poor knowledge, attitude,s and practice towards safe food handling practices in developing countries are common. The purpose of the study was to determine occupational hazards exposure and to assess knowledge, attitude, and practice towards meat safety among abattoir workers. Methods: A cross-sectional study was carried out on 216 abattoir workers from December 1st to February 30th, 2018 in Hawassa city. Systematic random sampling and semi-structured questionaries were used to collect data. Ethical approval for data collection was obtained from Hawassa University. Results: The study indicated that the majority of them had fair knowledge (42.3%), positive attitude (43.8%), and fair practice (45.3%) towards food safety and compliance with abattoir law. The study also revealed the positive relationship between knowledge and attitude (p<0.01); knowledge and practice (p<0.001), attitude and practice (p<0.01). The main three frequently reported occupational hazards were ergonomic hazard (19.7%), mechanical hazard (18.9%), and psychological hazard (16.7%). Conclusion: The study concluded that there was a poor level of knowledge, negative attitudes, and poor practices of abattoir workers towards meat handling, and compliance with the abattoir law. The study also found that occupational-related hazards most common in this work setting, which are persisting were needed to be improved, through training and occupational health and safety service.